Stress, health, and behavior - McCarty, Richard 1947- (The Guilford Press, 2023)
"Exposure to stressful life experiences can disrupt key regulatory systems in the body and contribute to a variety of negative health outcomes. This authoritative text takes a biopsychosocial approach to understanding the role of stress in alcohol use disorder, posttraumatic stress disorder, depression, cardiovascular disease, Type 2 diabetes, cancer, and other chronic diseases. It presents cutting-edge knowledge about how stressors are conceptualized and measured; connections to disease processes; systemic racism as a significant, ongoing stressor for people of color; and factors that promote resilience. For each of the disorders discussed, proven and promising stress-targeted clinical interventions are reviewed. Student-friendly features include an end-of-book glossary and an extensive bibliography to facilitate in-depth study of selected topics of interest. "-- Provided by publisher.